ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN NAGAN RAYA - Hasan, Ishak (Universitas Teuku Umar, 2018)
This study aims to analyze the effect of economic growth on open unemployment rate in Nagan Raya District. The data used is secondary data obtained from the Central Bureau of Statistics (BPS) of Nagan Raya District and other relevant agencies that have relevance to the subject matter of the research. This research uses Simple Linear Regression analysis model. The variables used are Open Unemployment Rate Y (dependent variable) and economic growth X (independent variable). The results showed that Growth of Economy Affects Against Reduction of open unemployment rate in Nagan Raya District. Based on t test shows that economic growth has t count > t table (4.213 > 2,570). then Ho is rejected and Ha accepted. so that individually the variable of economic growth positively influence to the decrease of open unemployment in Nagan Raya District. Based on the calculation of correlation coefficient and determination of the writer can explain that the value of the coefficient of determination of 0.780 which can be interpreted that 78.0 percent can be explained by the variable of economic growth (X). While the rest of 22.0 percent can be explained by other variables outside the research model. The result of linear regression equation can be seen that the value of constant is positive value is equal to 3,076 This constant value describes if independent variable (economic growth) equal to zero hence level of open unemployment in Regency of Nagan Raya will decrease as many as 3,076 soul.Keywords: Economic Growth and Open Unemployment